Youth Knowledge of Tobacco 21 and its Association With Intention to Use Tobacco. Issue 2 (18th August 2020) - Dai, Hongying; Chaney, Lisa; Ellerbeck, Edward; Friggeri, Ressa; White, Nancy; Catley, Delwyn
Abstract: Background: Raising the minimum legal age (MLA) of tobacco sales from 18 to 21 (Tobacco 21 [T21]) has recently been implemented nationwide as a method to reduce tobacco use, but empirical data on youth knowledge of T21 policies and related pathways to tobacco use are limited. Methods: Data were collected from the 2018 Kansas Communities That Care Student Survey. Knowledge of the MLA was compared between T21 and non-T21 regions using a quasi-experimental design. Logistic regression and mediation analysis were conducted to assess the association between knowledge of the MLA, influencing factors, and intention to use tobacco. Results: Of 16 949 students (aged between 11 and 18) completing the T21 survey, fewer students responded correctly about the MLA in T21 than in non-T21 regions (37.4% vs. 46.3% responded correctly, 27.6% vs. 24.2% responded incorrectly, respectively). In T21 regions, Hispanics and students who support T21 were more likely to respond correctly about the MLA. Among current non-tobacco users in T21 regions, students who responded correctly about the MLA were less likely to report intention to use tobacco (adjusted odds ratio [AOR] = 0.7, 95% confidence interval [CI]: [0.6–0.8]) than those who responded incorrectly. The pathway from knowledge of the MLA to intention to use tobacco was significantly mediated by increased support for T21 ( p = .002), perceived difficulty in accessing cigarettes ( p = .042), and reduced susceptibility to peer influence ( p = .027). Conclusions: Knowledge of the MLA was inversely associated with intention to use tobacco among youth. Educational campaigns to raise awareness and support for T21 among youth may improve the impact of T21 policies. Implications: This study examined youth knowledge of the MLA to purchase tobacco products, and whether knowledge of the MLA was associated with reduced intention to use tobacco. It also examined other influencing factors (eg, perceived support for T21) and potential mediation pathways linking knowledge of the MLA with intention to use tobacco. Given the nationwide adoption of T21, educational campaigns to promote knowledge of the policy may improve its impact.